The answer is -7
no to sure though
Answer:
8) answer=5 9)answer=15
Step-by-step explanation:
all you have to do is replace in the following formula
![\sqrt{(x2-x1)^{2}+ (y2-y1)^{2}} =d](https://tex.z-dn.net/?f=%5Csqrt%7B%28x2-x1%29%5E%7B2%7D%2B%20%28y2-y1%29%5E%7B2%7D%7D%20%3Dd)
Where
X1: is the first number of the first point
Y1: is the second number of the first point
X2: is the first number of the second point
Y2: is the second number of the second point
you replace in the formula and solve
I attach solution
Work shown above! Box a is 240 lbs Box b is 120 and Box c is 150 lbs hope this helps c:
28.4
Explanation
(Multiply the numbers) 3.24 x 10= 32.4
(Subtract the numbers) 32.4 - 4= 28.4